A imagem da mulher no romance “Um amor anarquista” de Miguel Sanches Neto: um relato sob múltiplas óticas - Beira, Juracema Carzino (2015)
This work involves the field of literature and has as its main objective finding out how woman is represented in the novel “Um amor anarquista”, by Miguel Sanches Neto, published in 2005. Based on biographic research, this work discusses the historical context of European immigration in Brazil, the creation of an anarchist community in Palmeira, as well as basic concepts of anarchism and feminism. This research aims at discussing women’s representation in the novel.